PROCUREMENT RISK MANAGEMENT AND SUPPLY CHAIN PERFORMANCE OF SACHET WATER PRODUCERS IN MAKURDI, BENUE STATE, NIGERIA - Adamu, Yavga Bundepuun; Abanyam, Emmanuel Igbawase; Hanmaikyur, John Tyoapine (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2025)
This study examined the impact of procurement risk management on the supply chain performance of sachet water producers in Makurdi, Benue State, Nigeria. Utilizing a census approach, data were collected from the entire population of 169 staff through a validated questionnaire, with a reliability coefficient of 0.854. Logit regression analysis, performed using SPSS Version 26, provided insights into the effects of various risk management practices on supply chain outcomes. The analysis reveals that contractual risk analysis (CRA) significantly enhances supply chain performance, with an estimate (B) of 0.498, a Wald statistic of 4.567, and a significance level of 0.002, indicating that each unit increase in CRA improves performance odds by approximately 3.645 times. This means that for each unit increase in contractual risk analysis, the likelihood of improved supply chain performance multiplies by 3.645. In contrast, supplier reliability assessment (SRA) shows no significant impact, with an estimated coefficient (B) of 0.065, a Wald statistic of 0.021, and a significance level of 0.885, suggesting limited effect on performance. Supplier risk assessment (SUA) is found to be statistically significant with an estimated coefficient (B) of 0.553, a Wald statistic of 2.608, and a significance level of 0.018, which implies that each unit increase in SUA boosts performance odds by about 2.738 times. Supply chain visibility (SCV) and sourcing and category management practice (SCM) show minimal impact, with estimates of 0.055 and -0.303 respectively, both statistically insignificant. The study conclude that not all procurement risk management practices contribute equally to supply chain performance as shown in the result, hence it is recommended among others that focusing on robust contractual risk management and comprehensive supplier risk assessments while considering resource reallocation from less impactful practices will be helpful for the studied firms.